2023
DOI: 10.1111/jgs.18312
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic evaluation of events and benefits of lipid lowering in older adults (PREVENTABLE): Trial design and rationale

Abstract: Whether initiation of statins could increase survival free of dementia and disability in adults aged ≥75 years is unknown. PREVENTABLE, a double‐blind, placebo‐controlled randomized pragmatic clinical trial, will compare high‐intensity statin therapy (atorvastatin 40 mg) with placebo in 20,000 community‐dwelling adults aged ≥75 years without cardiovascular disease, disability, or dementia at baseline. Exclusion criteria include statin use in the prior year or for >5 years and inability to take a statin. Potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…This may also explain, in part, why our study showed a greater reduction in mortality risk compared to CVD events, similar to prior work by our group 7 . The ongoing STAtins in Reducing Events in the Elderly (STAREE) trial in Australia and Pragmatic Evaluation of Events and Benefits of Lipid‐Lowering in Older Adults (PREVENTABLE) trial in the United States, both primary prevention trials of atorvastatin vs placebo for adults ≥70 and 75 respectively, will definitively elucidate the role of statins for primary prevention among older adults, including those with frailty 31,32 …”
Section: Discussionsupporting
confidence: 85%
“…This may also explain, in part, why our study showed a greater reduction in mortality risk compared to CVD events, similar to prior work by our group 7 . The ongoing STAtins in Reducing Events in the Elderly (STAREE) trial in Australia and Pragmatic Evaluation of Events and Benefits of Lipid‐Lowering in Older Adults (PREVENTABLE) trial in the United States, both primary prevention trials of atorvastatin vs placebo for adults ≥70 and 75 respectively, will definitively elucidate the role of statins for primary prevention among older adults, including those with frailty 31,32 …”
Section: Discussionsupporting
confidence: 85%
“…18,19 Both STAREE and PREVENTABLE are well positioned to examine this issue with respect to statin use, as both trials will include frail participants, will have suitable data to build a FI and are ascertaining cognitive function. 6,7 In summary, the results of Orkaby et al are reassuring, suggesting that the primary prevention benefits of statins for CVD observed in middle age populations likely also extend to older adults, including those 75 years or older and those more likely to be frail. 9 One must still be cautious with this interpretation, as it is conceivable that the observed differences reflect educational and socioeconomic differences between patients that did or did not initiate a statin.…”
mentioning
confidence: 99%
“…6 In the United States, the Pragmatic Evaluation of evENTs And Benefits of Lipid-lowering in oldEr adults (PREVENTABLE) trial plans to enroll 20,000 community-dwelling adults ≥75 years free of cardiovascular disease and is similarly comparing atorvastatin 40 mg versus placebo on a primary outcome of survival free of dementia and persistent disability, with incident CVD being a secondary outcome. 7 The results from STAREE and PREVENTABLE are highly anticipated but are not expected for several years. STAREE has recently completed enrollment and expects at least three more years of follow-up.…”
mentioning
confidence: 99%
See 2 more Smart Citations